Urokinase plasminogen activator receptor (CD87) expression of tumor-associated macrophages in ductal carcinoma in situ, breast cancer, and resident macrophages of normal breast tissue - Hildenbrand, Ralf; Wolf, Georg; Böhme, Beatrix; Bleyl, Uwe; Steinborn, Andrea (Journal of leukocyte biology, 1999)
Macrophages concentrate urokinase-type plasminogen activator (uPA) at the cell surface by expressing urokinase receptors (uPAR) in order to focus the pericellular space plasminogen-dependent proteolysis important in matrix remodeling and cell movement. This study examines the uPAR levels of tumor-associated macrophages (TAM) of invasive breast carcinomas, of TAMs from ductal carcinoma in situ (DCIS) and of macrophages derived from normal (non-tumor) breast tissue. TAMs from invasive breast carcinomas (n = 30), from DCIS (n = 12), and macrophages from normal breast tissue (n = 30) were cultured and immunocytochemically phenotyped by using a panel of antibodies. Urokinase receptor levels were determined by Western blot analysis and in cell-free supernatants by enzyme-linked immunosorbent assay. Urokinase receptor cell surface fluorescence intensity was determined by FACS and by confocal laser scan microscopy. Urokinase-receptor mRNA was detected by in situ hybridization. TAMs of invasive breast carcinomas and of DCIS possess significantly elevated uPAR levels compared with macrophages derived from normal breast tissue. Conclusions: activated macrophages with elevated uPAR levels belong to inflammatory areas in close vicinity of infiltrating and non-infiltrating (DCIS) tumor cells. Blood monocytes that possess elevated uPAR-levels may be selectively recruited from the bloodstream to inflammatory sites close to carcinoma cells, and/or breast cancer and precursor lesions may induce elevated uPAR-levels in TAMs by paracrine interactions. J. Leukoc. Biol. 66: 40-49; 1999.
Gesehen am 23.06.2022